Bioactivities, Phytochemicals and Pharmacophore Analysis of Nipa Palm (Nypa fruticans Wurmb) Sugar Extracts - Wan Mazliena Aliana, Wan Sabri (Universiti Malaysia Sarawak (UNIMAS), 2021)
Nipa palm (Nypa fruticans Wurmb) sugar is used as a sweetener for local people especially in Sarawak. It was processed by using nipa palm sap as a raw material as it was cooked for several hours until it became brown syrup. Nipa palm sugar or widely known as gula apong. Nipa palm (N. fruticans Wurmb) sugar was extracted by using different solvents which were methanol (MeOH), ethanol (EtOH), water (H2O), ethyl acetate (EtOAc) and hexane (Hex). All of the extracts were used to determine the moisture content, ash content, pH of the nipa palm sugar. Phytochemical screening was conducted in order to know the presence of the active compounds in the extracts. MeOH, EtOH and H2O extracts were tested positive for the presence of saponins, tannins, terpenoids, flavonoids, phenolic compounds, reducing sugar and non-reducing sugar. The antioxidant activity of extracts was evaluated by using 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity and the results showed that nipa palm sugar extracts possessed antioxidant properties which were EtOH (IC50 = 200.6 μg/mL), MeOH (IC50 = 208.3 μg/mL), H2O (IC50 = 569.8 μg/mL), EtOAc (IC50 = 1336.0 μg/mL) and Hex (IC50 = 4917.0 μg/mL). Alpha-amylase inhibition assay was performed by comparing with the acarbose and the results for the extracts were EtOH (IC50 = 109.40 μg/mL), MeOH (IC50 = 124.20 μg/mL) and H2O (IC50 = 545.10 μg/mL). The antioxidant activity and alpha-amylase inhibition assay resulted that EtOH extract showed high inhibition for both assay. All of the extracts showed the low toxicity level against the brine shrimp (Artemia salina). The LigandScout 4.3 software based on Computer-Aided Drug Design (CADD) was used to identify the value of the nipa palm sugar in the pharmaceutical industry. Based on the ligand-based pharmacophore analysis, arginine showed the highest fit-value compared to other chemical constituents in nipa palm sugar, which is 89.42, with the interactions of 4 HBA, 4 HBD and 1 PI. Structure-based